Previsão e monitoramento do evento extremo da cheia de 2009 - Vale, Roseilson Souza do (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
The present study evaluates the possible impact of sea surface temperatures (SSTs) of the Atlantic and Pacific oceans on the high-water regime of Amazonian Rivers and to analyze the development of the extreme flood in 2009. The year 2009 presented unusual climatic conditions. From the beginning of 2009 the water levels of the rivers in the Amazon region was monitored, which permitted an analysis of the movement of the flood along the mainstem of the Solimões-Amazonas. Once the hydrological event in 2009 has been characterized, statistical instruments and data on water levels, SSTs and OLR (Outgoing Longwave Radiation) have been configured to model this event by its principal hydrological stations in Amazonia. The analysis of the flood in 2009 indicated an intense increase in the western part of the basin at the beginning of the year. Afterwards the flood wave move eastwards in a smoothed form due to the presence of large floodplain areas (várzeas), but contributing that many Amazonian rivers passed over their historical flood levels. The study on the influence of SSTs and the high-water regime of the rivers was performed with the aim to construct regressive stochastical forecast models. The correlation between the studied hydrological stations and the regions of the Atlantic and Pacific oceans, indicated a spatial variation within the basin. From the six analyzed stations, models for Óbidos and Manaus were constructed with the capacity to forecast flood events with three and one months in advance, respectively. This study indicates that still improvements can be incorporated in the model to forecast floods.
Keywords: Eventos extremos; Evento de cheia; Temperatura da superfície do mar